Low insertion loss air-coupled ultrasonic transducer with parallel laminated piezoelectric structure - Xiaoyu Wang; Xun Gong; Congcong Li; Ranran Wu; Zhenglin Chen; Haodong Wu; De Zhang; Xun Cao (AIP Advances, 2020)
This work presents a low insertion loss air-coupled ultrasonic transducer with a parallel laminated piezoelectric structure. The relevant parameters of this structure are theoretically analyzed. For overcoming the enormous acoustic impedance mismatch between the piezoelectric material and air, a 1–3 connectivity piezoelectric composite, and a stack of two low acoustic impedance matching layers are adopted. The experimental results show that the insertion loss of −17.5 dB is obtained under the pitch-catch mode with the length of the air column of 50 mm by selecting a suitable air-coupled ultrasonic transducer combination. The insertion loss improvement is 3.8 dB compared with a monolayer piezoelectric structure with an identical active area.